Análise das competências e da complexidade no espaço ocupacional das Funções Gratificadas no IFSP Campus Araraquara - Minale, Matheus Bossi (2018)
The objective of this dissertation is to analyze the competencies and characteristics of the complexity in the occupational space of the Gratified Functions in a public organization of high school, technical, technological and higher education. Being inserted in increasingly complex contexts, public organizations are faced with an increasing need to adapt their people management systems. However, there are still few studies that propose practical solutions to the challenges in the public service. Given this scene, a case study is carried out at the IFSP Campus Araraquara through the correlated analysis of multiple data sources, which are: the systematization of a theoretical reference on competencies and complexity aligned with the context of public administration; the analysis of the routines and of three institutional documents of the organization; and the questionnaires applied to the federal employees that occupy the Gratified Functions object of the study (coordinators) and their respective chiefs (directors). The analysis of the data from the proposed methodology highlights the behavioral competencies as the most important for these functions, also shows that the complexity of the work perceived by the directors is greater than the perceived by the occupants of the functions. Given these facts, the main results of the research at the IFSP Campus Araraquara point out that the work of the Gratified Functions is increasingly linked to the decisions made by its employees, thanks to the importance given to the capacity for relationship, communication and adaptation to change, as well as, that the directions and coordinations must work together in order to align institutional expectations with deliveries in the occupational space. Finally, this research aims to contribute to the proposal of a range of competencies in order to understand the issues and challenges of people management in public organizations.